Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm having trouble solving this equation for $x$:

$$-\frac{1}{2}x^2 + 2x + 5 = 0$$

What's the steps to take to solve it?

Thanks.

share|improve this question
    
The equation in the question.. –  Cypras Feb 7 '13 at 23:02
    
Not sure how to format properly? It should be -1/2 –  Cypras Feb 7 '13 at 23:04
    
@Cypras: the equation is not written properly and it is not clear what you meant as the LaTex is a bit hosed. Regards –  Amzoti Feb 7 '13 at 23:04
    
Are you familiar with the quadratic formula? –  Gerry Myerson Feb 7 '13 at 23:05
    
Multiply by -2 and use the ABC formula –  Slugger Feb 7 '13 at 23:05

3 Answers 3

up vote 3 down vote accepted

$$x^2-4x-10=0$$ $$x^2-2\cdot x\cdot2+2^2-2^2-10=0$$ $$x^2-2\cdot x\cdot2+2^2=4+10$$ $$(x-2)^2=14$$ $$x-2=\pm \sqrt{14}$$ $$x=2\pm \sqrt{14}$$

share|improve this answer
    
+1 simple but leading approach. –  B. S. Feb 8 '13 at 17:39
    
@Thank you very much Babak. –  Adi Dani Feb 8 '13 at 18:30

If you multiply by $-2$ you get $x^2-4x-10=0$, then you can use the quadratic formula to get $x=\frac 12 (4 \pm \sqrt {16+40})=2 \pm \sqrt {14}$

share|improve this answer
    
How did you get 14? –  Cypras Feb 7 '13 at 23:11
    
sqrt(16 + 40) = sqrt(56) = sqrt(2 * 2 * 14) = 2 * sqrt(14) –  oks Feb 7 '13 at 23:14
1  
@oks: I am not sure OP will see your comment. You can preface it with <at>Cypras as Rustyn Yazdanpour did to make sure s/he does. You can only notify one user with the at sign per comment. –  Ross Millikan Feb 7 '13 at 23:18
    
@Rustyn That makes no sense to me. Square root of 56 equals 7.4something? How do you change it like that? –  Cypras Feb 7 '13 at 23:20
1  
@Cypras: Rustyn Yazdanpour is doing arithmetic under the square root sign, then using the fact that $\sqrt{ab}=\sqrt a \cdot \sqrt b$. The $40$ in the next to last should be $14$. –  Ross Millikan Feb 7 '13 at 23:26

If you multiply $$-\frac{1}{2}x^2 + 2x + 5 = 0\tag{1}$$

by $-2$ you get $$x^2-4x-10=0$$ Using the quadratic formula: $$ax^2 + bx + c = 0 \iff x = \frac{1}{2a}\left(-b \pm \sqrt{b^2 - 4ac}\right),$$ where in this case, $a = 1,\;b= -4,\; c = -10$ we have $$x=\frac 12 (4 \pm \sqrt {16+40})=2 \pm \sqrt {14}\tag{2}$$

Walking through the simplification of $(2)$

$$x = \frac12 (4 \pm \sqrt{16 + 40}) \;=\; \frac12(4 \pm \sqrt{56})\; = \;\frac12 (4 \pm \sqrt{4\cdot 14}) \;=\; \frac12 (4 \pm \sqrt{4}\sqrt{14})\;$$ $$ = \;\frac12 (4 \pm 2\sqrt{14})\;=\; \frac 12 \cdot 4 \pm \frac12 \cdot 2\sqrt{14}\;\; = \;\;2 \pm \sqrt{14}$$

share|improve this answer
    
We, here, denote the discriminate by $\Delta=b^2-4ac$. + –  B. S. Feb 9 '13 at 5:34

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.